The Culturally Responsive Teaching Approach in Developing Indonesian Language Teaching Modules Based on Lombok Local Culture - Evi Sulistiana; Yeni Artanti (Universitas Cokroaminoto Palopo, 2026)
This study aims to develop, determine the feasibility, practicality, and effectiveness of a Lombok-based Indonesian language teaching module for seventh-grade junior high school/MTs students. This type of research is research and development (R&D) with a 4D model (define, design, develop, disseminate). The validation test was conducted by two experts, namely a subject matter expert and a media expert, while the practicality test involved a limited trial involving 16 students and a field trial involving two classes, each with 29 students in the experimental and control classes. Then, the effectiveness test was conducted using SPSS, such as normality test, homogeneity test, independent sample t-test, and N-Gain. The data were analyzed using quantitative and qualitative approaches. The results showed that the teaching module was developed based on four main stages and covered four learning materials, namely descriptive texts, folk poetry texts, fantasy story texts, and procedural texts. Lombok locality was used as the text in each learning activity. The feasibility assessment by experts obtained an average score of 92.10% with a category of very feasible, while the practicality assessment by teachers and students was 81.88% and 84.14% respectively with a category of very practical. The effectiveness test using the Independent Sample t-Test showed a significance value of 0.000 (< 0.05), which means that there was a significant difference between the experimental and control classes. The N-Gain value of 0.72 (high category) with a 64.95% increase in learning outcomes shows that the teaching module is effective. This module is considered capable of improving learning outcomes, strengthening conceptual understanding, and fostering awareness of local culture in Indonesian language learning. This finding contributes to the innovation of Indonesian language learning that is adaptable to culture, thereby enriching the learning experience and cultural insight of seventh grade junior high school/MTs students.